Analysis of Students 'Mathematic Ability in Using Open Ended Teaching Materials on Class VII Function Relations Materials - Ninik Diah Wulandari; Yus Mochamad Cholily; Rizal Dian Azmi (Department of Mathematics Education University of Muhammadiyah Malang, 2020)
This study aims to describe students' written mathematical communication skills in using open ended-based teaching materials on class VIII function relations material. The type of research used is descriptive qualitative. The research subjects were 5 students of class VIII E, SMP Negeri 12 Malang. Data collection techniques in this study in the form of tests and interviews. Research results obtained by students in the category of high mathematical communication skills have the ability to convert questions into set notations, students are quite capable of transforming mathematical information into images and students are able to use mathematical information to solve problems. Students with written mathematical communication skills are having sufficient ability to convert mathematical information into the form of set notations, students are less able to convert mathematical information into images and students are able to use mathematical information to solve problems. Students with low communication skills seen from students are not able to change the questions into set notations, students are less able to convert mathematical information into images and students are unable to be less able to use mathematical information to solve problems.